STUDI KEANEKARAGAMAN JENIS BURUNG DI TAMAN WISATA ALAM BIPOLO, DESA BIPOLO, KECAMATAN SULAMU, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR. - Krisel Wirgayan Ndoluanak; Ludji Michael Riwu Kaho; Astin Elise Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
This research was conducted to determine the diversity of bird species. This research was conducted at TWA Bipolo, Bipolo Village, Sulamu District, Kupang Regency, East Nusa Tenggara. This research was held for 1 month, from March to April 2020. This study used the observation method and the Mackinnon method. The data were processed using the Shannon Wiener diversity index (H'), Evenness Index (E), Frequency (F), Margalef Wealth Index (R), and vegetation analysys. The results showed that the birds found in Bipolo TWA were 23 species of birds from 16 families with a total of 219 individuals. The most common bird species found was the Cucak Kutilang (Pynonotus aurigaster) with 29 individuals and the least found was the Delimukan Zamrud (Chalcophaps indica) with 1 individually. The results of the calculation of bird species diversity in Bipolo TWA were calculated using the Shannon Wienner index of 2.85 (H'), TWA Bipolo is moderate (H' 2-3). The evenness index of bird species in TWA Bipolo is moderate with a value (E=0.52). The highest frequency of bird species in the TWA Bipolo area is Cucak Kutilang (Pynonotus aurigaster) with a frequency value of 1.66, relative frequency of 19.03% and the lowest frequency of availability is the Delimukan Zamrud bird (Chalcophaps indica) with a frequency value of 0.09, the relative frequency of 1.03 %. The bird species wealth index in TWA Bipolo of (R = 4.08) is quite high. The plants that dominate in the area guava species with the Important Value Index of 438.988 and are found in all categories.